A NEW FORMATION OF POSTMODERNISM: SITUATIONAL AESTHETIC - Renkci, Tugba (ISTANBUL KULTUR UNIV, 2014)
Aesthetics, in the process up to the present, has been used in many fields and different theories. Today's aesthetic point of view is very different. This study is handled some of current approaches to art movement and groups that is based on the basics of Dadaism. Aestheticized is discussed in terms of truth and reality of life with the culture industry. Also, by generating the influence of the culture industry, differences in these two concepts have been introduced and research made on strategy and tactics which is an important element of the situational aesthetics. In addition to this, researches have been done about effects of culture industry of situational aesthetic and approaching today's postmodern theory and structuring in contemporary art. This issue is examined in terms of today's art economy of situational aesthetic on several cases. The purpose of this article is sophisticatedly investigated situational aesthetics that is in scope of contemporary art.
Keywords: Aesthetic; Postmodern; Situational Aesthetic; Strategy; Tactic; Cultur Industry; Situations International; Art